If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -8) = x Reorder the terms: x(-8 + x) = x (-8 * x + x * x) = x (-8x + x2) = x Solving -8x + x2 = x Solving for variable 'x'. Reorder the terms: -8x + -1x + x2 = x + -1x Combine like terms: -8x + -1x = -9x -9x + x2 = x + -1x Combine like terms: x + -1x = 0 -9x + x2 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-9 + x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-9 + x)' equal to zero and attempt to solve: Simplifying -9 + x = 0 Solving -9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + x = 0 + 9 x = 0 + 9 Combine like terms: 0 + 9 = 9 x = 9 Simplifying x = 9Solution
x = {0, 9}
| 2x^2+3x=30 | | x-2(-4)=10 | | 1/2(3x+2)-1/2(x+6)=5 | | f=9/5*43+32 | | y-16/2+y-9/7=-8 | | =x+15 | | 15=7.5+2.5y | | 4+18p-2=9p+50-7p | | =2x+15 | | t=4g+4vforg | | -7+7x+x=-39 | | x/11-(-8)=19 | | 3z-9=2z+6 | | graphx+y=3 | | -2=r-10 | | 2x+5(1)=30 | | 3z-9=2z+2 | | 2x+3=y-x | | x=7.5+2.5(-2) | | =9x+15 | | -4=5p-6p | | 3/10-w+3/5w=4/5 | | (5z+1.2)+9.9= | | 19=8x+3-6x | | 5.3+1u=3.2u-2.7 | | y=9x+15 | | 15=5y+-2x | | 36p+12=-16+7p | | 1.5s-1.2-1s=0.5 | | 10b-3b=39 | | 2(15+-2.5y)+5y=30 | | 6(x+1)-11=53 |